Organ-based characterization of B cells in patients with systemic lupus erythematosus - Wang, Yunan; Zhao, Rui; Liang, Qian; Ni, Shiwen; Yang, Mei; Qiu, Liwei; Ji, Juan; Gu, Zhifeng; Dong, Chen (Frontiers in Immunology, 2025)
Systemic lupus erythematosus (SLE) is a chronic, inflammatory, and progressive autoimmune disease. The unclear pathogenesis, high heterogeneity, and prolonged course of the disease present significant challenges for effective clinical management of lupus patients. Dysregulation of the immune system and disruption of immune tolerance, particularly through the abnormal activation of B lymphocytes and the production of excessive autoantibodies, lead to widespread inflammation and tissue damage, resulting in multi-organ impairment. Currently, there is no systematic review that examines the specificity of B cell characteristics and pathogenic mechanisms across various organs. This paper reviews current research on B cells in lupus patients and summarizes the distinct characteristics of B cells in different organs. By integrating clinical manifestations of organ damage in patients with a focus on the organ-specific features of B cells, we provide a new perspective on enhancing the efficacy of lupus-targeted B cell therapy strategies.